2011
DOI: 10.1038/nmeth.1699
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and phosphoproteomic comparison of human ES and iPS cells

Abstract: Combining high mass accuracy mass spectrometry, isobaric tagging, and novel software for multiplexed, large-scale protein quantification, we report deep proteomic coverage across multiple biological replicates and cell lines. We applied this method to study four human embryonic stem cell and four induced pluripotent stem cell lines in biological triplicate, a 24-sample comparison resulting in the largest set of identified proteins and phosphorylation sites in pluripotent cells to date. The statistical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
261
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(286 citation statements)
references
References 48 publications
18
261
2
Order By: Relevance
“…3A). Interestingly, three independent studies revealed that RbBP5 S350 is phosphorylated in vivo (Christensen et al 2010;Phanstiel et al 2011;Shiromizu et al 2013). To determine the impact of RbBP5 phosphorylation on WRAD formation, we ectopically expressed constructs corresponding to either wild-type RbBP5 or an RbBP5 S350A mutant in fusion with a Flag tag in HEK293 cells.…”
Section: Disruption Of Ash2l/rbbp5 Interaction Impairs Mll1 Enzymaticmentioning
confidence: 99%
“…3A). Interestingly, three independent studies revealed that RbBP5 S350 is phosphorylated in vivo (Christensen et al 2010;Phanstiel et al 2011;Shiromizu et al 2013). To determine the impact of RbBP5 phosphorylation on WRAD formation, we ectopically expressed constructs corresponding to either wild-type RbBP5 or an RbBP5 S350A mutant in fusion with a Flag tag in HEK293 cells.…”
Section: Disruption Of Ash2l/rbbp5 Interaction Impairs Mll1 Enzymaticmentioning
confidence: 99%
“…In regards to their pluripotency, ability to form the three embryonic germ layers, and overall global gene expression programs [2][3][4], the two stem cell classes appear to be very similar [3,5]. Nevertheless, others have observed subtle differences between their RNA levels, DNA methylation, protein expression and protein phosphorylation [6]. Some of these differences are attributed to the current limitations of the various reprogramming processes used in the generation of iPSCs [7,8] and may contribute to the variable efficiencies with which hiPSCs can undergo differentiation [9].…”
Section: Introductionmentioning
confidence: 99%
“…The method of stable isotope labeling has greatly propelled large-scale, quantitative analysis (26)(27)(28)(29)(30)(31). While generally robust, these techniques can yield spotty data for certain peptide and protein groups-mainly those present at low abundances.…”
Section: Resultsmentioning
confidence: 99%